Pengembangan Gim Gradien untuk Memahamkan Siswa pada Materi Gradien Garis Lurus - Arie Wibowo (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
The use of learning media games in learning mathematics can make students more interested and easy to understand concepts in mathematics lessons. The aim of this research is to produce a game to help students understand the gradient of a line through two points. The development of this game using the GeoGebra software version 5 uses the Thiagarajan 4D development research method which consists of four steps, namely defining, designing, developing, and disseminating. To produce a game that is valid, practical, and effective, a series of trials are carried out, namely expert testing and development testing. The results of the validity test show the game's validity score is 3.76 with a very valid category. The practical test conducted on 5 students showed a 100% presentation in the very practical category. The effectiveness test using One-Group Pretest-Posttest Design shows that this media is effective in improving student learning outcomes.